2007
DOI: 10.1186/1477-7525-5-30
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of adult retinoblastoma survivors in the Netherlands

Abstract: Background: To assess the quality of life (QoL) and predictors thereof in Dutch adult hereditary and non-hereditary retinoblastoma (RB) survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 32 publications
(33 reference statements)
7
70
1
3
Order By: Relevance
“…Physical well-being Differences in physical well-being between survivors and comparison groups ranged from large to none across most studies [28,30,[32][33][34][35][36][37][38][39][40]. Two studies reported survivors as scoring their physical well-being as better than the general population [29,31].…”
Section: Methodsmentioning
confidence: 90%
See 4 more Smart Citations
“…Physical well-being Differences in physical well-being between survivors and comparison groups ranged from large to none across most studies [28,30,[32][33][34][35][36][37][38][39][40]. Two studies reported survivors as scoring their physical well-being as better than the general population [29,31].…”
Section: Methodsmentioning
confidence: 90%
“…Most studies found small to no significant differences between survivors and comparison groups with respect to psychological well-being [28,30,33,34,36,37,39,40]. Five studies reported higher psychological well-being for survivors [29,31,32,35,38].…”
Section: Psychological Well-beingmentioning
confidence: 86%
See 3 more Smart Citations